When Time is Money. - Adam, Barbara (Theoria: A Journal of Social & Political Theory, 2003)
Focuses on the rationalities of time in the theory and practice of work in the U.S. Principle economic strategies that have heralded benefits to society; Association of the industrial way of life with time and speed; Consequences of decontextualization, commodification, and the relation to time as money.